17p13.3 Microduplication, a Potential Novel Genetic Locus for Nonsyndromic Bilateral Cleft Lip and Palate. (May 2015) - Ibitoye, Rita M.; Roberts, Joanna; Goodacre, Tim; Kini, Usha
Cleft lip and palate (CLP) is a relatively common congenital malformation. The etiology is complex and postulated to be a combination of genetic and environmental factors. The genetic loci for nonsyndromic CLP remain poorly characterized. Two families have recently been reported with a chromosome 17p13.3 microduplication and CLP. We report a third family with four individuals affected by nonsyndromic bilateral CLP and a 350-kb chromosome 17p13.3 microduplication (17:1, 113, 102–1, 461, 838). Our family possesses the smallest overlapping chromosome 17p13.3 microduplication associated with CLP, narrowing down the critical region for this potential new genetic locus for CLP.